Fatakhova , Nargiz - (:unkn) unknown (My University, 2026)
Nargiz Rafael Fatakhova graduated from the Azerbaijan University of Architecture and Construction (AzUAC) with a Bachelor’s degree in Economics and Management of Construction in 2011 and a Master’s degree with distinction in Management in 2014. She began her professional career at AzUAC in 2009 as an Operator in the Human Resources Department. Since 2018, she has been working as a Lecturer at the Department of Economic Theory and Marketing, becoming a full-time Lecturer in 2019. She teaches courses in Entrepreneurship and Business, Economic Regulation, Macroeconomics, and Microeconomics. In 2023, she was awarded the degree of Doctor of Philosophy (PhD) in Economics after successfully defending her dissertation, The Impact of Innovation and Scientific Technologies on the Development of the Construction Sector of the Republic of Azerbaijan. Dr. Fatakhova is the author of more than 50 scientific publications, one monograph, one teaching manual, and three course programmes. Her research interests include innovation, scientific and technological development, and the economics of the construction sector.